Philosophy of biology before biology - Bognon-Küss, Cécilia; Wolfe, Charles T. 1970- (Routledge, 2019)
The use of the term "biology" to refer to a unified science of life emerged around 1800 (most prominently by scientists such as Lamarck and Treviranus, although scholarship has indicated its usage at least 30-40 years earlier). The interplay between philosophy and natural science has also accompanied the constitution of biology as a science. Philosophy of Biology Before Biology examines biological and protobiological writings from the mid-eighteenth century to the early nineteenth century (from Buffon to Cuvier; Kant to Oken; and Kielmeyer) with two major sets of questions in mind: What were the distinctive conceptual features of the move toward biology as a science? What were the relations and differences between the "philosophical" focus on the nature of living entities, and the "scientific" focus? This insightful volume produces a fresh but also systematic perspective both on the history of biology as a science and on the early versions of, in the 1960s in a post-positivist context, the philosophy of biology. It will appeal to students and researchers interested in fields such as history of science, philosophy of science and biology
Description based on online resource; title from digital title page (viewed on March 26, 2019)
Keywords: Biology / Philosophy / History / 18th century; Biology / Philosophy / History / 19th century; Philosophy of nature / History / 18th century; Philosophy of nature / History / 19th century